Parliamentary Procedure: Lay on the Table - James E. Dyer (EDIS)
The motion to Lay on the Table is used to temporarily delay action on a pending question while something else of immediate urgency needs consideration, or when another item of business needs to be addressed before consideration of the pending question. This 2-page fact sheet was written by James E. Dyer and published by the UF Department of Agricultural Education and Communication, January 2013.